The kaleidoscopic city : Hong Kong, mission, and the evolution of global Pentecostalism - Mayfield, Alex R., 1989- (Waco, Texas : Baylor University Press, 2023)
"A thematic examination of Pentecostalism in Hong Kong in the early twentieth century as a test case for the study of modern Chinese Pentecostalism"--
Introduction: The cipher city : mapping Hong Kong in Pentecostal mission history -- 1. The gateway city : Pentecostal mission and the struggle for center -- 2. The holy city : denominational Identity and Pentecostal missionary structures -- 3. The soul-saving city : inducement, education, and evangelistic institutions -- 4. The heathen city : Pentecostal spirituality in Hong Kong's religious marketplace -- 5. The women's dity : gender and the Pentecostal missionary enterprise -- Conclusion: The kaleidoscopic city : Hong Kong and the evolution of global Pentecostalism -- Appendix: Digital methodology.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 15, 2023).
eBooks on EBSCOhost
Keywords: Hong Kong (China) -- Church history -- 20th century; China -- Church history -- 20th century; Pentecostalism -- China -- Hong Kong -- 20th century; Pentecostalism -- History; China -- Church history; Mouvement charismatique -- Histoire; Chine -- Histoire religieuse; Mouvement charismatique -- Chine -- Hongkong -- Histoire; Chine -- Histoire religieuse -- 20e siècle.; Mouvement charismatique -- Chine -- Hongkong -- 20e siècle.; Pentecostalism; China -- Hong Kong; Church history; History